An Assessment of Alpha-Amylase as Salivary Psychological Stress Marker in Relation to Temporomandibular Disorders among a Sample of Dental Students - Sarmad Q Ali; Raja Hadi (College of Dentistry/ University of Baghdad, 2015)
Background: University dental students perceived a higher level of stress prior to the final exam associated with raised salivary alpha-amylase levels which could be considered as a useful noninvasive biomarker for measuring acute stress. Using a Helkimo anamnestic and clinical dysfunction scoring for temporomandibular disorders can give a better insight about the association of this marker and temporomandibular disorders. The aim of this study was to evaluation level of salivary alpha-amylase in stressor students with temporomandibular disorders and the relation between the marker in relation to temporomandibular disorders severity. This might give a better understanding to the role of psychological stress as an etiological factor for developing temporomandibular joint problems. Materials and Methods: A total eighty participants aged between 20 to 24 were recruited for this study. The participants were University dental students under graduate students at final examination period who were examined and gave saliva samples in final examination period. Salivary assay kits as alpha-amylase was used to measure those variable and a Helkimo anamnestic and clinical dysfunction scoring for temporomandibular disorders. Results: The group of participants with stress and temporomandibular disorders showed significantly higher levels of salivary alpha-amylase than the control group, the salivary alpha-amylase has statistically non-significant correlation with Helkimo anamnestic categories (Di-I mild, Di-II moderate and Di-III severe. Salivary alpha-amylase levels show non-significant and weak association with two categories of clinical dysfunction criteria in Helkimo index system, which are Muscle pain and temporomandibular joint pain on palpation. Conclusion: This study concluded that University students perceived a high level of stress before the final examination. Salivary alpha-amylase is now the stress biomarker that is most often used to measure acute stress. Helkimo anamnestic and clinical dysfunction scoring criteria for still the pioneer for measuring a TMD.